The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-09352010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical profiles of rats submitted to experimental poisoning with Tityus serrulatus venom

Abstract: The hematological and biochemical profiles of newly weaned rats submitted to experimental poisoning with T. serrulatus venom were evaluated. Fifteen recently weaned male Wistar rats (mean weight 130g) were distributed into three equal groups (n = 5). Animals in the control group (group A) received a subcutaneous injection of 400µL of ultra-pure water, while those in the experimental groups received, by identical route, 400µL of a solution containing 100µg (group B) or 450µg (group C) of scorpion venom dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
2
1
1
Order By: Relevance
“…These results contrast with those of earlier studies in which scorpion venom was found to be capable of triggering polycythaemia in dogs [2930] and rabbits [7], as well as reducing platelet counts in rats [25]. Overall, these results indicate that sheep may be more resistant to scorpion venom toxicity than these other species, reinforcing their potential for use as anti-venom producing animals.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…These results contrast with those of earlier studies in which scorpion venom was found to be capable of triggering polycythaemia in dogs [2930] and rabbits [7], as well as reducing platelet counts in rats [25]. Overall, these results indicate that sheep may be more resistant to scorpion venom toxicity than these other species, reinforcing their potential for use as anti-venom producing animals.…”
Section: Discussioncontrasting
confidence: 91%
“…A decrease in serum amylase values in G2 occurred following the third and sixth doses, but this decrease was not significant when compared to other groups. Other studies have reported serum amylase increases in scorpion-envenomed patients [72325], suggesting that the decrease observed in our study may be specific to the ovine species.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In rat with leukocytopenia, folate, Zn, Fe, or Cu deficiency may occur, which results in suboptimal production of blood cells. Another possibility is the abnormality in the bone marrow as a producer of blood cells [18]. Viral infections that attack the immune system can also cause this condition, but cannot be confirmed without further examination [19].…”
Section: Table 2 Blood Cell Values For Each Individualmentioning
confidence: 99%
“…Análises de ureia e creatinina também foram realizadas. A peçonha de Ts induziu aumento dos dois analitos indicando disfunção renal nos animais, conforme já reportado (Pinto et al, 2010b;Pucca et al, 2012). Estudos histológicos em ratos demonstram que a peçonha de Ts e sua toxina majoritária (Ts1) induzem congestão renal com pequenas áreas hemorrágicas (Correa et al, 1997 (Ribeiro et al, 2010).…”
Section: Análise Do Número De Células E Produção De Citocinas De Linfunclassified